Techno-economic analysis of Xylitol, Citric Acid and Glutamic Acid biorefinery scenarios utilizing sugarcane lignocellulose - Ozudogru, H. M. Raoul (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.